DINASTI KEPALA DESA (Studi Tentang Survivabilitas Dinasti Politik di Desa Puput Kecamatan Simpangkatis Kabupaten Bangka Tengah) - , SAMSUL KOMAR ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purposes of this study is to reveal the existence of a local politics dynasty that has ruled Puput village since 1971 until now, time of this study. The domination of the head of village dynasty called Mustofa Dynasty then was obtained through the victory in every the head of village election (Pilkades). The duration of Mustohfa Dynasty domination realizing the authors that there is a strong political force network and loyally support forthe existence of the dynasty. For this study, the authors used qualitative research methods,with in-depth interviews and secondary data collection in accordance with the needs of the study. The formulation of the problem being the authors question is : Whya family is able to maintain the position of head ofvillage in two different government regimes ? In order to answer these research questions, the authors combine these two theoretical frameworks as analytical framework : village elite contestation and patron-client. Both theoretical frameworks complete each other, where the village elite contestation is used to looks the forms of local political contestation along the Mustohfa dynasty. While the patron-client relationship is used to uncover patterns of Dynasty Mustohfa with supporters (clients) to gain political support in order to win every electoral contestation in Puput village. The study found that the legitimacy of power obtained as the ability to maintain the solidity of the nuclear family (elite dynasty) and the patronage resources particularly strong economic sustain Mustohfa Dynasty.That are coupled with the ability to maintain the solidity of external (outside the elite dynasty) identified as clientelistic networks that never decay, and even tend to strengthen. They have high solidity in favor one of its elite to be a candidate of the head of village,because they were never fragmented by their own political ambitions. If fragmentationever happens, it is only just touching clientelistic network which can always be consolidated through a personalized approach patronage and redistribution of resources. Means that the existence of Mustohfa Dynasty at the top of power in the Puput Village caused by the ability to reproduce the patronage resources are converted through clientelistic networks became a massive and sustainable political support. That argument asserts that political dynasty survivability depend on ability to manage three things :first, sustainability of the core followers clientelism network consists of family kindship and closest men in organizational and govermental structure of village. Second, control ovel economic resources and accumulation of wealth owned.Third, ability mantaining clientelism network solidity with the forces in outside of the organizational and govermental structure, used to be mass mobilization machine to gain power and as âshieldâ to protect the power had been achieved. Nevertheless patronage resources distribution un designed to converting every political support in every the head of village electionin Puput village. Formal position recruitment to support the performance of head of village, labor recruitmentto support economic activities and the benevolence that being Mustohfa Dynasty tradition, increasinglystrengthen theexistingclientelisticnetworks.